2020
DOI: 10.1177/0959683620981689
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of the guanaco (Lama guanicoe) in Patagonia during Late Pleistocene–Holocene and its importance for prehistoric human diet

Abstract: The great importance of the guanaco ( Lama guanicoe) for the subsistence of the human populations of Patagonia during the Holocene has been demonstrated in numerous studies. This species is considered as the main prey of the hunter-gatherer groups of the Patagonian interior, indicating the existence of a strong ecological relationship of predator-prey type. Despite the importance of this ungulate for prehistoric human populations, its spatial distribution throughout the Holocene has not been systematically exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
12

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 76 publications
1
11
0
12
Order By: Relevance
“…In Northwestern Neuquén the trend is towards a high consumption of guanaco, being this species consumed in higher frequencies than expected by its potential distribution (Figure 2). The high contribution of guanaco to human diet in this area had been previously shown on the basis of isotopic and zooarchaeological data (Barberena, Prates, & de Porras, 2015; Gordón et al, 2018; Rindel, 2017), in line with the trend found for overall Patagonia (Moscardi et al, 2020; Rindel, Moscardi, & Perez, 2021). Likewise, pichi shows negative values of selectivity in this area, despite being consumed in considerable frequency, due to its extremely high potential distribution (mean = 0.99), suggesting that this species was partly ignored.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In Northwestern Neuquén the trend is towards a high consumption of guanaco, being this species consumed in higher frequencies than expected by its potential distribution (Figure 2). The high contribution of guanaco to human diet in this area had been previously shown on the basis of isotopic and zooarchaeological data (Barberena, Prates, & de Porras, 2015; Gordón et al, 2018; Rindel, 2017), in line with the trend found for overall Patagonia (Moscardi et al, 2020; Rindel, Moscardi, & Perez, 2021). Likewise, pichi shows negative values of selectivity in this area, despite being consumed in considerable frequency, due to its extremely high potential distribution (mean = 0.99), suggesting that this species was partly ignored.…”
Section: Discussionsupporting
confidence: 76%
“…The performance of each distribution model was evaluated using the area under the receiver operating characteristic (ROC) curve (AUC statistic; Elith & Leathwick, 2009). For a detailed review of these methods see Guisan et al (2017), and for an application in archaeology see Rindel, Moscardi, and Perez (2021).…”
Section: Methodsmentioning
confidence: 99%
“…The spatial distribution of different types of projectile point types of the latest Pleistocene and early Holocene from southern South America was estimated using the maximum entropy modeling approach implemented in the MaxEnt method 28 , 29 . This approach is widely used in paleoecology and archaeology because it is robust and based on presence-only data 28 , 29 , 72 , 73 . The dataset of projectile points used in the analyses consists of records with absolute dates—or highly reliable relative dates—and precise geographic locations.…”
Section: Methodsmentioning
confidence: 99%
“…In the study area, this Order is represented by camelids, specifically guanaco ( Lama guanicoe) present in this region throughout the Holocene until recent times. This species is one of the most represented in the zooarchaeological record in the region (Rindel et al, 2021). More recently, from historical times to the present, several artiodactyls species were present in the South American extensive Phylogeographical regions of Monte, Espinal, Patagonian desert, and other Andean landscape configurations; not only with the presence of guanacos but also with the introduced goats and sheep.…”
Section: Discussionmentioning
confidence: 99%